Generative mechanisms for student value perceptions: an exploratory case study. Issue 8 (14th September 2021) - Nicholson, Alex; Johnston, Paul
ABSTRACT: Despite ever-strengthening political rhetoric to the contrary, there can be little doubt that the holistic value of an undergraduate degree is far greater than merely its potential for employability enhancement. However, what is less clear is the extent to which fee-paying students perceive broader aspects of value, and how such value perceptions are formed. This paper outlines findings from an exploratory case study comprising six life history interviews in which past and present law students from a post-92 university in the UK were asked to explore how they perceive the value of their degree, specifically focusing on how and when such value perceptions might have been shaped by their life experiences. Through analysis of the resultant data, a wide range of possible 'generative mechanisms' were identified which may influence student value perceptions in this context. Generative mechanisms are not direct causes but things which have the potential to have a real-world impact given the right conditions. By understanding such mechanisms, legal education providers – and to a lesser extent also providers from other disciplines – can more effectively design and market their programmes to ensure that they deliver maximum value that is perceived within their markets.